6(y-5)=2(9-y)

Simple and best practice solution for 6(y-5)=2(9-y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(y-5)=2(9-y) equation:



6(y-5)=2(9-y)
We move all terms to the left:
6(y-5)-(2(9-y))=0
We add all the numbers together, and all the variables
6(y-5)-(2(-1y+9))=0
We multiply parentheses
6y-(2(-1y+9))-30=0
We calculate terms in parentheses: -(2(-1y+9)), so:
2(-1y+9)
We multiply parentheses
-2y+18
Back to the equation:
-(-2y+18)
We get rid of parentheses
6y+2y-18-30=0
We add all the numbers together, and all the variables
8y-48=0
We move all terms containing y to the left, all other terms to the right
8y=48
y=48/8
y=6

See similar equations:

| 2x+156=4x+192+ | | 3n+-1=8 | | 9m=-180 | | -7r-6=-6-7r | | 2(u-6)+3=11 | | 5y/6+1/2=9/4+y/4 | | x-77=9(2x+3)-2 | | 8x+16+32=90 | | 9(x-2)=7x+15 | | 6(y-2)-8y=-20 | | -13.6=1.1+x/5 | | −4=x5+6 | | 7(-3r+10)=-8r-8 | | 3(1+y)=5(y+1) | | 20√x+6+3=18 | | -66=-5x-7(-4x-7) | | -34=8y+6 | | 2−14a=38−2a2-14a=38-2a | | -12+a=60 | | 5(3k+9)-9k=k | | z+1.7=3.8 | | 9x-18=(3x-6) | | 10x+10=15+4x | | -8h=10h-9(-8h+10) | | z+1.7=3/8 | | 3b+5b=32 | | -5-8(7m+5)=-269 | | 6+4x+52=90 | | 25/(x+4)=5 | | -1=p-555 | | 10+4x=3(7+5x) | | 34=20+k |

Equations solver categories